1994
DOI: 10.5636/jgg.46.7
|View full text |Cite
|
Sign up to set email alerts
|

The GEOTAIL Magnetic Field Experiment.

Abstract: The Geotail spacecraft carries a high-resolution Magnetic Field Experiment to provide magnetic field data in the frequency range below 50 Hz. This experiment includes dual fluxgate magnetometers and a search coil magnetometer. Fluxgate sensors are mounted at distances of 4 m and 6 m from the spacecraft on a deployable mast to reduce spacecraft-generated noises. Both outboard and inboard fluxgate magnetometers have 7 automatically switchable ranges from ±16 nT to ±65536 nT (full scale) and resolutions equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
446
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(448 citation statements)
references
References 14 publications
2
446
0
Order By: Relevance
“…Following injection A1, open magnetic flux is closed, shrinking the polar cap, and the dayside reconnection rate is insufficient to return the flux to the pre-substorm level before the next expansion onset. Huang et al (2003b) identified injection A1 as a substorm through observations by GEOTAIL (Kokubun et al, 1994) of a travelling compression region related to plasmoid formation in the magnetotail as well as observations of proton flux enhancements by 1991-080 (16:00 MLT).…”
Section: Overviewmentioning
confidence: 99%
“…Following injection A1, open magnetic flux is closed, shrinking the polar cap, and the dayside reconnection rate is insufficient to return the flux to the pre-substorm level before the next expansion onset. Huang et al (2003b) identified injection A1 as a substorm through observations by GEOTAIL (Kokubun et al, 1994) of a travelling compression region related to plasmoid formation in the magnetotail as well as observations of proton flux enhancements by 1991-080 (16:00 MLT).…”
Section: Overviewmentioning
confidence: 99%
“…The 12 s resolution data from Geotail magnetometer [Kokubun et al, 1994] and the low-energy particle (LEP) experiment [Mukai et al, 1994] have been collected from 1998 to 2005. The LEP data on Geotail are over the energy range of several eV to 43 keV.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The intervals are 16:00±19:30 UT on 14 March (day 73) 1993, and 08:28±08:43 and 14:25±14:45 UT on 18 April (day 108) 1994. We used data from the magnetic-®eld (MGF) experiment (Kokubun et al, 1994) at 3-s resolution and the energetic particle (EPIC) instrument (Williams et al, 1994). EPIC consists of sensors ICS and STICS, and the time resolution is declared in each plot varying from 3 to 96 s. All the EPIC measurements are depicted as di erential¯uxes.…”
Section: Observations and Data Analysismentioning
confidence: 99%